APPRAISAL OF SOCIAL LISTENING STRATEGIES FOR BRAND IMAGE DEVELOPMENT OF GRAND CEREALS COMPANY PRODUCTS IN PLATEAU STATE - AYUBA JOHN RAMADAN; MELCHIZEDEC ONOBE (International Studies Journal)
Effective social strategies are crucial for organizations to monitor brand conversations, respond to customer feedback, and maintain a positive brand image. Grand Cereals is a leading food processing company in Nigeria, with a strong presence in Plateau State. Despite the importance of social listening in brand image development, there appears to be a dearth of research on the social listening strategies employed by Grand Cereals in Plateau State. The research was aimed at identifying how Grand Cereals and Oil Mills Ltd carryout social listening on their company products and to assess how Grand Cereals and Oil Mills Ltd engage their online customers on the social media and examine the emerging trends in content creation. The research took its leaning from the uses and gratification theory and media dependency theory. The research was an empirical one, with primary data gathered from twenty staff of the sales and marketing department of Grand Cereal and Oil Mills Ltd, Jos, Plateau State. The findings of the research revealed that Grand Cereals and Oil Mills Ltd has no official strategy for monitoring online conversations about their company products, in addition to the fact that the company has no official engagement strategy for their online customers. The research recommended that Grand Cereals should establish a robust social media presence. The company should also utilize social listening tools to monitor brand conversations, track customer feedback, and respond promptly to customer inquiries and complaints. The study recommended that Grand Cereals should encourage online engagement with their online customers.